PENEGAKAN HAK ASASI MANUSIA DALAM PANDANGAN TEORI NEGARA HUKUM - ST. Nirwansyah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The state itself creates its tools to implement power in a repressive manner and when that happens all forms of human rights violations are difficult to avoid. Herein lies the problem why in the end the community sued the state. The rule of law theory in principle supports guaranteeing life, freedom and property rights of the people and that the government must respect these human rights. The meaning of the social agreement lies in the guarantee of these rights. Human rights according to this way of thinking have what is called pre-constitutional nature. Human rights are received rights regardless of state ties (staatsverband). A state bond that does not guarantee human rights has actually lost the basis of its existence.